MULTI REPRESENTATION STRATEGY AS AN ALTERNATIVE ACTIVITY IN CLASSROOM ACTION RESEARCH ON TOPIC OF ALGEBRA AND ITS APLICATIONS - Hutagaol, Kartini (11th International Scholars Conference, 2016)
The article is related to the student representation at junior high school to explain the relation and difficulty in understanding the concept of math. The result on the field indicated that can often do the math exercise but they don’t understand about that. When the students were asked to give explanation of their answer, the students felt anxious in giving the answers. Looking at the problem, there must be awareness of the teacher with the real activities in a habitual situation to fix the students difficulties to understand the concept of math. However, teachers have to prepare the proper action to deal with problem one real action in the habitual situation to solve the problem is classroom action research. Multi representation strategy (SMR) is an alternative of classroom action research. By doing SMR, students can build their confidence through the types of chosen representation. Students felt appreciated, and understood, because the teachers appreciated their ideas, although they are simple (informal) but they can be taken into formal. So, the students don’t lose their confidence in giving their ideas. This is issue that must be considered by the stakeholders and teachers.